MINORITAS MUSLIM DALAM KONTESTASI IDENTITAS DI EROPA: Pemikiran Thariq Ramadhan dalam Meneguhkan Identitas Muslim Bercita Rasa Eropa - Zunly Nadia (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The Muslim diaspora in Europe turned out to give birth to an absurd identity for the Muslim community because they were in a new place that had different customs and cultures even the opposite of their home countries. A Muslim with his teachings that bind on the one hand and face the reality or European context on the other. This problem then made Tariq Ramadhan reformulate the identity of European Muslims through the sources of Islamic teachings themselves, so that they became a middle ground for European Muslim minorities who were previously in the opposite identity, namely living in the west out of the west or becoming Muslim without Islam.